2018
DOI: 10.3390/ijms19113491
|View full text |Cite
|
Sign up to set email alerts
|

Receptor Tyrosine Kinase-Targeted Cancer Therapy

Abstract: In the past two decades, several molecular targeted inhibitors have been developed and evaluated clinically to improve the survival of patients with cancer. Molecular targeted inhibitors inhibit the activities of pathogenic tyrosine kinases. Particularly, aberrant receptor tyrosine kinase (RTK) activation is a potential therapeutic target. An increased understanding of genetics, cellular biology and structural biology has led to the development of numerous important therapeutics. Pathogenic RTK mutations, dele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
165
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 233 publications
(165 citation statements)
references
References 252 publications
(269 reference statements)
0
165
0
Order By: Relevance
“…The EGFR, a transmembrane glycoprotein belonging to the ErbB family of RTKs, is over-expressed in different types of malignant tumours. [6] EGFR amplification and over-expression were found in more than 60% of primary glioblastomas, which leads to excitation of several signalling pathways, including PI3K/Akt and Ras/Raf/MAPK and subsequently proliferation, invasion and survival of tumour cells. [4,[7][8][9][10] Some reports have shown that expression of IRS-1 and IRS-2, two upstream modulators of IGF-1R/Akt pathway, are elevated in various types of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The EGFR, a transmembrane glycoprotein belonging to the ErbB family of RTKs, is over-expressed in different types of malignant tumours. [6] EGFR amplification and over-expression were found in more than 60% of primary glioblastomas, which leads to excitation of several signalling pathways, including PI3K/Akt and Ras/Raf/MAPK and subsequently proliferation, invasion and survival of tumour cells. [4,[7][8][9][10] Some reports have shown that expression of IRS-1 and IRS-2, two upstream modulators of IGF-1R/Akt pathway, are elevated in various types of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…The epidermal growth factor receptor (EGFR), also known as ErbB‐1, is a transmembrane glycoprotein belongs to the ErbB family of receptor tyrosine kinases (RTKs) that is over‐expressed in different types of human malignancies . Amplification and over‐expression of EGFR gene were found in more than 60% of primary glioblastomas and are believed to be linked to the proliferation, growth, angiogenesis and invasiveness in glioma cells .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Targeting of tyrosine kinases is a major cancer therapeutic strategy today. At the same time, unexpected endocrine and metabolic adverse effects of such therapies have been observed, and heightened vigilance is required.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic alterations in anaplastic lymphoma kinase (ALK), a member of the insulin receptor protein‐tyrosine kinase superfamily, are implicated in the pathogenesis of several human cancers. In non‐small‐cell lung cancer (NSCLC), ALK rearrangement occurs in approximately 3–7% of patients.…”
Section: Introductionmentioning
confidence: 99%